Pickering Emulsion Stabilized by Different Concentrations of Whey Protein–Cress Seed Gum Nanoparticles - Maryam Davtalab; Sara Naji-Tabasi; Mostafa Shahidi-Noghabi; Artur J. Martins; Ana I. Bourbon; Miguel A. Cerqueira (Foods)
Nanoparticles based on food-grade materials are promising materials to develop Pickering emulsions for food applications. Initially, this study focuses on the development of nanoparticles through the utilization of a soluble complex of whey protein concentrate (WPC) and cress seed gum (CSG), which were modified by calcium chloride (CaCl2) as a cross-linker. The response surface methodology was used to investigate the impact of different concentrations of WPC (1–4% w/v), CSG (0–1% w/v), and CaCl2 (1–3 mM) on particle size, polydispersity index (PDI), and Zeta potential. The optimum conditions for the production of CSG–WPC nanoparticles (WPC–CSG NPs) were 0.31% (w/v) CSG, 1.75% (w/v) WPC, and 1.69 mM CaCl2, resulting in nanoparticles with average size of 236 nm and Zeta potential of −22 mV. Subsequently, oil-in-water (O/W) Pickering emulsions were produced with different concentrations of WPC–CSG NPs in optimum conditions. The contact angles of the WPC–CSG NPs were 41.44° and 61.13° at concentrations of 0.5% and 1%, respectively, showing that NPs are suitable for stabilizing O/W Pickering emulsions. Pickering emulsion viscosity rose from 80 to 500 mPa when nanoparticle concentration increased from 0.5% to 1%. Results also showed that WPC–CSG NPs enable stable O/W Pickering emulsions during storage and thermal treatment, confirming that protein–polysaccharide NPs can provide a sufficient steric hindrance.